Транзисторные антенны-автогенераторы СВЧ-диапазона - Prudyus, I. N.; Hollynskyy, V. D.; Storozh, V. G. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
The results of the development of circuits and designs of oscillator antennas are presented, and the possibility of their application as motion sensors is considered. Experimental research results are provided. A sensor design is proposed in which increased sensitivity is achieved by reducing the influence of intrinsic noise. Radiation pattern switching of the oscillator antenna is used at a frequency where the noise level is insignificant.